2022
DOI: 10.3390/agronomy12030584
|View full text |Cite
|
Sign up to set email alerts
|

Application of Humic Substances in Agricultural Industry

Abstract: Increasing agricultural productivity and, in particular, the productivity of livestock is one of the primary tasks in the present stage of development of society. This involves rational feeding and the use of biologically active substances, including humic preparations that activate the digestive and metabolic processes in the animal, promoting the transformation of feed nutrients in assimilable form, raising daily milk production and weight gain, and can play an important role in solving this urgent problem. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Numerous research studies have demonstrated positive crop responses to HPs from various sources in fields, greenhouse, and controlled environmental studies (Rose et al, 2014;Nardi et al, 2021;Yang et al, 2021;Bezuglova and Klimenko, 2022). Ampong et al (2022) recently provided a comprehensive review on the significant positive impacts of humic acid (HA) on crop growth, yield, and soil physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research studies have demonstrated positive crop responses to HPs from various sources in fields, greenhouse, and controlled environmental studies (Rose et al, 2014;Nardi et al, 2021;Yang et al, 2021;Bezuglova and Klimenko, 2022). Ampong et al (2022) recently provided a comprehensive review on the significant positive impacts of humic acid (HA) on crop growth, yield, and soil physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Probably, the acidic nature of humic substances plays an essential role in their reactivity and performance in alkaline soils. The abundance of different functional groups in humic acid, especially acid functional groups like carboxyl, determines their adsorption capacities for HMs (Yang, Miao et al 2015, Bezuglova andKlimenko 2022). In expressing the effect of humic substances in the growth process of plants, the following have been reported: I) improvement in root formation and development of the assimilation apparatus (Canellas, Olivares et al 2002, Zandonadi, Santos et al 2010, Mora, Baigorri et al 2012, changes of phosphate metabolism and energy transfer (Rosa, Silva et al 2018, de Castro, Berbara et al 2021, acceleration in protein metabolism (Vaughan 1974, Vaccaro, Ertani et al 2015, increase in the intensity of respiration processes, photosynthesis, and water exchange and increasing the concentration of chlorophyll and ascorbic acid (Liu, Cooper et al 1998, Lotfi, Kalaji et al 2018, Shamsullah 2020.…”
Section: Effects Of Applied Humic Acidmentioning
confidence: 99%
“…They are among the most reactive soil components and natural chelating agents that may be applied as a fertilizer, plant growth promotor, and nutrient carrier (Stevenson 1994, Park, Kim et al 2013, Dubey, Raha et al 2019. In fertile soils rich in humus, the content of humic acid reaches 5-7% (Bezuglova and Klimenko 2022). Complexation of HMs with humic substances can enhance their phyto-available fraction in soil and stimulate plant growth Zhu 2006, Bezuglova andKlimenko 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, however, HS are being increasingly applied in practical agriculture. This is explained by the fact that humic substances have high physiological activity, which is expressed in stimulating the growth and development of both plants and animals [5].…”
Section: Introductionmentioning
confidence: 99%